Contribution of spatial intelligence, adversity intelligence, to the creativity of vocational school students - Ramadani, Ali Hasbi; Ekohariadi, Ekohariadi; Anifah, Lilik; Suhartini, Ratna; Arizal, Heru; Rahayu, Imami Arum Tri; Nugroho, Yuli Sutoto (Intelektual Pustaka Media Utama, 2025)
Today’s industry requires graduates of mechanical engineering expertise programs who have high creativity. The purpose of this study is to describe how the influence of spatial intelligence, adversity intelligence, on the creativity of vocational students of the mechanical engineering expertise program. The urgency of this research is as a basis for consideration of talent interest search, selection of student admissions in vocational schools, which has been general. This research is a type of ex post facto involved 206 students of the mechanical engineering expertise program in Surabaya city in Indonesia. The data collection techniques used are tests and questionnaires. Data analysis using structural equation modeling (SEM) with SmartPLS application. The results of the analysis showed that: i) spatial intelligence and adversity intelligence had a positive and significant effect on student creativity with scores of 7.3% and 87.5%, respectively and ii) simultaneously spatial intelligence and adversity intelligence contributed to increasing student creativity by 81.4%. Implications this study can help in the development of a selection system for new student admissions tailored to the needs of mechanical engineering expertise programs. In addition to the development of a more diverse curriculum to integrate learning approaches that allow students with various types of intelligence to develop optimally.